1995
DOI: 10.1002/j.1550-8528.1995.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Food Deprivation Decreases Extracellular Dopamine in the Nucleus Accumbens: Implications for a Possible Neurochemical Link Between Weight Loss and Drug Abuse

Abstract: POTHOS, EMMANUEL N, LUIS HERNANDEZ AND BARTLEY G HOEBELChronicfooddeprivationdecmases extracellular dopamine in the nucleus accumbens: implications forapossibleneurochemicallink betweenweight loss and drug abuse. Obes Res. 1995;3(Suppl4):525S-529S. InratsreducedtoSO% ofnormalbodyweight(n=9),the basal levels of extracellular dopamine (DA) in the nucleus accumbens (NAC), as determined by microdialysis,decmased significantly to 33% (mean f SEM) of their normal baseline (pX.01). BasalextracellullarDA did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…Rats that were tested just once with drug after 5 or 6 weeks of eating high-fat chow were significantly more sensitive (i.e., both limbs of the dose-response curve shifted leftward) than rats eating standard chow to apomorphine-induced and quinpirole-induced yawning, respectively, indicating increased sensitivity at D3 and D2 receptors. These behavioral data parallel results from neurochemistry studies showing that food restriction decreases extracellular dopamine concentration in the nucleus accumbens (Pothos et al 1995), increases dopamine D2 receptor binding (Thanos et al 2008), and increases coupling between D2 receptors and G proteins (Carr 2002). Moreover, rats eating high-fat chow have decreased extracellular dopamine in the nucleus accumbens (Rada et al 2010) and increased D2 receptor binding (South and Huang 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Rats that were tested just once with drug after 5 or 6 weeks of eating high-fat chow were significantly more sensitive (i.e., both limbs of the dose-response curve shifted leftward) than rats eating standard chow to apomorphine-induced and quinpirole-induced yawning, respectively, indicating increased sensitivity at D3 and D2 receptors. These behavioral data parallel results from neurochemistry studies showing that food restriction decreases extracellular dopamine concentration in the nucleus accumbens (Pothos et al 1995), increases dopamine D2 receptor binding (Thanos et al 2008), and increases coupling between D2 receptors and G proteins (Carr 2002). Moreover, rats eating high-fat chow have decreased extracellular dopamine in the nucleus accumbens (Rada et al 2010) and increased D2 receptor binding (South and Huang 2008).…”
Section: Discussionsupporting
confidence: 79%
“…It has been demonstrated that with food intake dopamine release is enhanced in the circuits that mediate the pleasurable aspects of the eating (Volkow et al 2011). However, decreased body weight aft er chronic food deprivation has been shown to be associated with a decrease of dopamine levels (Pothos et al 1995). Th is suggests that increased food intake aft er chronic food deprivation and weight loss may represent a compensatory mechanism to restore the baseline dopamine levels .…”
Section: Role Of the Reward Systemmentioning
confidence: 99%
“…Nevertheless, only few studies have investigated the possibility of stress induced changes in brain DA receptors in animal models [14,15]. However, contrasting results reported by these studies do not permit any firm conclusion on the effects of stress on DA receptors.…”
Section: Introductionmentioning
confidence: 98%